Teacher Professional Development During the Pandemic Through the Simultaneous Beginner Teacher Induction Program at SMK Muhammadiyah 1 Ngadirejo - Moh Ihsan Firdaus; I Imron (Urecol Journal. Part G: Multidisciplinary Research, 2022)
This evaluation research aims to determine; (i) an overview of the implementation of the novice teacher induction program at SMK Muhammadiyah 1 Ngadirejo; (ii) a description of the ability of novice teachers who have participated in PIGP in planning lessons, implementing lessons and assessing student learning outcomes in Temanggung Regency during the pandemic. This type of research is qualitative that leads to field research (field research). The research was conducted in a naturalistic manner, with the researcher as the main instrument. The research process was carried out by conducting direct field observations/observations, interviews with school principals, waka curriculum, Islamic religious education teachers and waka students who were used as purposive samples of the research object. And to strengthen the opinion, the literature analysis method (library research) is used, namely the study of various scientific sources such as scientific articles in the form of journals, books, and other literature in accordance with the studies discussed. The results showed that (i) The description of the novice teacher induction program at SMK Muhammadiyah 1 Ngadirejo in terms of planning and preparation for the novice teacher induction program was well implemented. (ii) An overview of the implementation of the novice teacher induction program at SMK Muhammadiyah 1 Ngadirejo which is well implemented n. (iii) The description of the implementation of the novice teacher induction program at SMK Muhammadiyah 1 Ngadirejo in terms of the ability of teachers who have participated in PIGP in adapting to the work climate and school culture, planning lessons, implementing learning and assessing student learning outcomes very well during the pandemic.